The performance of married and single-mother entrepreneurs: evidence from Malaysia / Fatimah Sahva Abd. Hadi … [et al.] - Abd. Hadi, Fatimah Sahva; Mohd Hussin, Mohd Yahya; Abdul Razak, Azila; Muhammad, Fidlizan (Division of Research and Industry Linkages, UiTM Melaka, 2014)
This paper focuses on two core objectives. Firstly, it aims at exploring the profile of successful married and single-mother entrepreneurs who have been fruitfully run their business for at least 10 years under the scheme offered by Amanah Ikhtiar Malaysia (AIM). Secondly, it sought to empirically compare the performance of both groups from the objective (financial) and subjective (non-financial) angles especially after the replacement of existing schemes into the new one in 2003. About 403 respondents which comprise of 202 married and 201 single-mother entrepreneurs represent the sample of this study who participated in the survey exercise. The respondents considered for this study were restricted to the beneficiaries of AIM in the state of Perak particularly in Manjung Branch which is among the largest number of targeted groups. The data were collected using a self administered questionnaire, which is adopted, from several sources. The average annual sales for the last three years (2011-2013) were used to represent objective performance while subjective measure comprises 11 items. The descriptive analysis was employed to provide the general summary of the findings while the independent-sample t-test was applied to compare the performance of interested groups. The findings revealed that the performance of married entrepreneurs were better than the opposite group from the perspectives of both objective and subjective. Based on the result, some recommendations were proposed together with the some limitation of the study which provides help in charting direction for future research.